(untitled) (AYUSHDHARA, 2021)
Tabkheer-i-meda has been described as reflux of acid from stomach in the Unani classical literatures. This disease is characterized by various symptoms like indigestion, pain in abdomen, suppression of thrust, burning sensation in the epigastrium, anorexia, nausea and acid reflux etc. In modern medicine, Gastro-esophageal Reflux Disease (GERD) is defined as symptoms or mucosal damage produced by the abnormal reflux of gastric contents into the esophagus or beyond, into the oral cavity (including larynx) or lungs. The objective of the present study was to evaluate the efficacy of Safoof-i-Tabkheer on the patients suffering with associated symptoms of Tabkheer-i-Meda (Gastro-esophageal Reflux Disease). Patients were advised orally 5grams of Safoof-i-Tabkheer with water twice daily after the meal. It was observed that after the treatment, all associated symptoms of Tabkheer-i-Meda/ GRED including retrosternal burning, epigastric pain acidic brash and anorexia were significantly (p<0.05) reduced. The percentage reduction in retrosternal burning, acidicbrash, epigastric pain and anorexia were 53.89%, 51.56%, 48.53% and 40.65% respectively as compared to base line. No adverse effect of drug was found. Highly significant improvements (p<0.001, paired t test) in all associated symptom of the disease suggest that the results are really due to the therapy. On the ground of above observation, it can be concluded that the Unani pharamacopieal formulation ‘Safoof-i-Tabkheer’ is very effective and safe in the treatment of Tabkheer-i-Meda.